Teoria naturalizada do Direito: um debate metodológico com Brian Leiter e seus críticos - BRITO JUNIOR, Valdenor Monteiro (Universidade Federal do Pará, 2018)
The objective of this study is to discuss the methodology and ontology of general jurisprudence, whose aim is to elucidate the ontological nature of the Law, considering a defense of the naturalized jurisprudence. In opposition to the conceptual approach prevalent in contemporary legal theory, focusing about conceptual analysis and resource to intuitions, some theoreticians have accept empirical approaches that resource to sociological and anthropological insights to advance our understanding about the nature of Law. Among these empirical approaches, there is the defense of the naturalization of the general jurisprudence by Brian Leiter, discussing the Quine’s methodological naturalism whose point is the continuity between philosophy and science. The naturalized jurisprudence is founded on the resource to the conceptual schemas that are presupposed by our best scientific theories about the social human behavior for advancing the discussion about the real nature of Law. The criticism against these naturalized methodology and the limits of the Leiter’s version for naturalized jurisprudence are discussed and, in order for answer and/or account these objections, I propose a modified version of naturalized jurisprudence that it is more robust than the Leiter’s one, because it begins from less controversial premises and it conforms to contemporary analytic metaphysics and social ontology.